THE EFFECT OF CORRECTIVE SURGERY OF SCOLIOSIS ON CERVICAL LORDOTIC AXIS - ALDO CALADO; JULIANO RODRIGUES DOS SANTOS; JOSE ALEXANDRE CUNHA BAPTISTA; ANTONIO CARLOS MONTEIRO BRACONI; GUILHERME GALITO HENRIQUES; DANUSA DE MELO ROZINDO; JEFFERSON SOARES LEAL (Coluna/Columna)
ABSTRACT Objectives: To quantify the changes in cervical sagittal alignment of patients with adolescent idiopathic scoliosis (AIS) who underwent surgical treatment. Methods: Retrospective study of radiographic data analysis. Data were collected from 25 radiographs of patients with AIS, and 18 cases were included. The mean age was 15.2 years (13-17 years); all subjects were female, operated from March 2010 to October 2015. Pre and postoperatively, cervical lordosis (C2-C7), thoracic kyphosis (T5-T12) and lumbar lordosis (L1-S1) were measured. Scoliotic curves were analyzed and measured in anterior posterior views by the Cobb method and classified according to the Lenke classification. Results: Eighteen adolescent patients were evaluated with a mean follow-up of 31.3 months. There was a negative correlation (-0.613) between post-surgical and pre-surgical cervical lordosis variation, that is, the largest the angulations obtained, on average, the greatest the reductions. Thus, the correlation becomes positive when compared to postoperative period (0.579). Conclusion: We concluded that the correction of adolescent idiopathic scoliosis did not bring about statistically significant changes in the cervical spine, with respect to angle values. Lordotic cervical curves with greater angular value showed a greater variation in the postoperative period, resulting in a better biomechanical balance.